Medicine in Egypt at the time of Napoleon Bonaparte - Russell, Thomas G (BMJ Group, 2003)
The scientists and doctors who accompanied Napoleon to Egypt in 1798 undertook a survey that is one of the great intellectual achievements of the 19th century. It left a record of the health and wellbeing of the people, especialy in Cairo